Analyzing the Four State Vocational High School students’ perceptions of English, English Training, and Its Future - Alamsyah, Aam; Santosa, Santosa; Mutaat, Mutaat; Abidin, Zaenal; Supriyanto, Edy; Try Gustary, Devian; Laesa Oktaviani, Anggit; Mundi Astuti, Theresia; Darmawan, Radik (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
As part of the annual community service to help improve the school students' English skills, Technocrat Foreign Language School Tangerang conducted a community service in The Four State Vocational High School in Tangerang Regency, Banten. The English training emphasized improving the students' English communicative skills and their interest in practicing the language. The survey research, which succeeded in the training, indicated some important findings, such as the positive perceptions toward the English training, the perceived importance of English for the student's future careers, the importance of English subjects/courses in higher education as well as in employment. Specifically, the role of English in the hospitality, service, retail, and creative industry will be imperative. Of the four skills, speaking was deemed the most important skill to learn for employment. Concerning their future career, the students expected to have a non-English teaching career after graduating from college. The present study attempted to highlight the issue of the English training, potential employability, and the perceived important skill needed by the vocational high school graduates so that they can have more chances to work in the above industries. Further study should identifiy more skills specifically needed in the above industries so that the amount of unemployment from vocational high school graduates can be reduced.